Ultrafast click chemistry with fluorosydnones. - Liu, H; Audisio, D; Plougastel, L; Decuypere, E; Buisson, D; Koniev, O; Kolodych, S; Wagner, A; Elhabiri, M; Krzyczmonik, A; Forsback, S; Solin, O; et al. (Wiley, 2016)
We report the synthesis and reactivity of 4-fluorosydnones, a unique class of mesoionic dipoles displaying exquisite reactivity towards both copper-catalyzed and strain-promoted cycloaddition reactions with alkynes. Synthetic access to these new mesoionic compounds was granted by electrophilic fluorination of σ-sydnone Pd(II) precursors in the presence of Selectfluor. Their reactions with terminal and cyclic alkynes were found to proceed very rapidly and selectively, affording 5-fluoro-1,4-pyrazoles with bimolecular rate constants up to 10(4)  m(-1)  s(-1) , surpassing those documented in the literature with cycloalkynes. Kinetic studies were carried out to unravel the mechanism of the reaction, and the value of 4-fluorosydnones was further highlighted by successful radiolabeling with [(18) F]Selectfluor.